Aplicações do Comsol no estudo de nanopartículas plasmônicas - SILVANO, Gustavo Leite (2018)
The resolution of problems involving nanostructures requires the use of numerical methods due to its mathematical complexity. Among the existing methods, one can cite the Finite Element Method (FEM) and the Method of Moments (MoM). In this work it will be performed an analysis of various nanoparticles, using the commercial software COMSOL Multiphysics 4.2a for solution of differential equations using the Finite Elements Method. In some cases, the solutions obtained are compared with a program developed in MatLab, using Method of Moments. In this way, the results are more convincing due to the comparison of the methods. Among the tests, we have the classic problem of the dipole and monopole transported to the nanometer scale, then the implementation of an optical transmission line (OTL) and finally the simulation of graphene composite structures. Simulations will analyze the main characteristics of the particles, ranging from the efficiency of transmission, reflection coefficient, input impedance, electric field and absorption cross section, thus having a good idea of the behavior of such antennas according to their geometry, thus being useful during the design of resonant structures.